“The Pedestrian” and “Guest”: The Taoist Life Consciousness in Classical Chinese Poetry - Sixian, Li (Sinología hispánica. China Studies Review, 2024)
Both pedestrian and guest are not rare in classical Chinese poetry. It is reasonable to interpret pedestrian and guest as person on the road or away from home in some classical Chinese poems. However, considering the relevant Taoist classics and Taoist life consciousness, pedestrian and guest should be interpreted as the living person, not the man walking on the road, in the poems of mourning the dead, worshiping the ancestors, explaining the relationship between the individual and world, or expressing the insights related to Buddhism. It is not an accidental, but an important topic in ancient poetry. The adoption meaning of living person can make the work more profound and touching and the logic of the poems is clearer and more coherent.